Sustainable Livelihood of Peatland Dwellers in the Mukah Watershed, Sarawak, Malaysia - Peter, Songan; Gabriel Tonga, Noweg; Wan Sulaiman, W. H.; Murtedza, Mohamed (UUM, 2007)
A large area of peatland in Sarawak occurs in Mukah Division. Although, considered unsuitable for the cultivation of certain crops, peatlands have been used by the local communities for subsistence agriculture and sago cultivation for generations. When the Land Custody Development Authority (LCDA) allocated 30,000 hectares of land for sago cultivation in the Mukah watershed, opportunities to improve and sustain the livelihood of the communities were eagerly projected. Has this strategy improved and sustained the livelihood of the communities living in the Mukah watershed? Prior to this, what strategy options have they been adapting to sustain their livelihood? A socioeconomic survey was conducted on a sample of 300 respondents from seven selected villages in the Mukah watershed. The socioeconomic profile and the present socioeconomic activities, as well as the socio-cultural aspects related to these activities were examined. The study also provided some strategies and recommendations on how to further develop and sustain the livelihood of the local communities in order to prevent further deterioration of peatland in the Mukah watershed.